Lipid-based systems with precipitation inhibitors as formulation approach to improve the drug bioavailability and/or lower its dose: a review - Kovačević Mila; Gašperlin Mirjana; Pobirk Alenka Zvonar (Acta Pharmaceutica)
Lipid-based systems, such as self-microemulsifying systems (SMEDDS) are attracting strong attention as a formulation approach to improve the bioavailability of poorly water-soluble drugs. By applying the “spring and parachute” strategy in designing supersaturable SMEDDS, it is possible to maintain the drug in the supersaturated state long enough to allow absorption of the complete dose, thus improving the drug’s bio-availability. As such an approach allows the incorporation of larger amounts of the drug in equal or even lower volumes of SMEDDS, it also enables the production of smaller final dosage forms as well as decreased gastrointestinal irritation, being of particular importance when formulating dosage forms for children or the elderly. In this review, the technological approaches used to prolong the drug supersaturation are discussed regarding the type and concentration of polymers used in liquid and solid SMEDDS formulation. The addition of hypromellose derivatives, vinyl polymers, polyethylene glycol, polyoxyethylene, or polymetacrylate copolymers proved to be effective in inhibiting drug precipitation. Regarding the available literature, hypromellose has been the most commonly used polymeric precipitation inhibitor, added in a concentration of 5 % (m/m). However, the inhibiting ability is mainly governed not only by the physicochemical properties of the polymer but also by the API, therefore the choice of optimal precipitation inhibitor is recommended to be evaluated on an individual basis.